Development of Karakalpak Literature of the 21st Century - Maratovna, Otarbaeva Fatima (International Journal on Integrated Education, 2023)
in this article we analyze the very idea of the Karakalpak literature, as well as how it educates each person, while it develops the speech of any person using its traditional methods. With this, we consider what developed in Karakalpak literature in the 21st century.